Pengaruh Online Customer Review dan Online Customer Rating Terhadap Kepercayaan Konsumen (Studi Kasus Pengguna Shopee Mahasiswa Fakultas Ekonomi Universitas Nahdlatul Ulama Al Ghazali Cilacap) - Galang Mauludan; Hakim Hakim; Syafi’ah Syafi’ah (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to determine the effect of Online Customer Review and Online Customer Rating on Consumer Trust among Shopee users, particularly students of the Faculty of Economics, Nahdlatul Ulama Al Ghazali University, Cilacap. The increasing trend of online shopping among students demands a deeper understanding of the factors that shape consumer trust in e-commerce platforms. This research employs a quantitative method with an associative approach, and the data were collected through questionnaires distributed to 80 respondents. The data were analyzed using multiple linear regression analysis along with several classical assumption tests, including the normality test, multicollinearity test, heteroscedasticity test, and coefficient of determination (R²) test. The results indicate that Online Customer Review and Online Customer Rating have a positive and significant effect on Consumer Trust, both partially and simultaneously. The coefficient of determination (R²) value of 0.514 shows that 51.4% of the variation in Consumer Trust can be explained by the two variables, while the remaining 48.6% is influenced by other factors not examined in this study. Thus, the better the reviews and the higher the ratings given by consumers, the greater their trust in the Shopee platform